Left Lobe Hepatocellular Carcinoma in Non-Alcoholic Fatty Liver Disease Patient: A Case Report - Inayah, Ninda Nurul; Astariyani, Thaibah; Batubara, Raya Henri; Nikita, Ester Grace; Irwan, Khair El Nisa; Putri, Kirei Aulia; Handayani, Lisa; Palambang, Sira Sappa (Jurnal Kedokteran Brawijaya, 2024)
Hepatocellular Carcinoma (HCC) is the second most common cause of death from cancer worldwide, affecting more men than women with a ratio of 2:1. Approximately 70–90% of HCC patients have risk factors such as chronic liver disease and liver cirrhosis. Another significant risk factor is non-alcoholic fatty liver disease (NAFLD). We report a case of left lobe hepatocellular carcinoma in a 54-year-old woman who presented with heartburn and shortness of breath, with a history of hypertension but no alcohol consumption. Chest X-ray revealed cardiomegaly without pulmonary congestion. A whole abdominal CT scan identified a left lobe hepatic tumor measuring ± 11x12x13 cm. Pathology examination revealed an epithelial mass with infiltrative, trabecular, acinar, and solid arrays, indicative of a malignant liver tumor.